Chinese Drug Users' Abstinence Intentions: The Role of Perceived Social Support. (October 2018) - Liu, Liu; Wang, Huimin; Chui, Wing Hong; Cao, Liqun
This study investigated the relationship between Chinese drug users' perceived social support and their intentions for choosing abstinence. Both bivariate and multivariate analyses were performed with 3, 239 drug users, especially heroin (427) and methamphetamine (890) users. All participants were from multiple Chinese compulsory drug treatment institutions. Perceived support from friends was the factor that showed a strongest positive relationship with Chinese drug users' abstinence intentions. The positive influence from family support on the willingness to seek and choose abstinence was not as great as scholars have suggested, which challenges previous research findings. Methamphetamine users had a significantly lower chance of pursuing abstinence, but their abstinence intentions were positively related to perceived support from friends. Comparatively, all types of perceived social support had no significant influence on heroin users' abstinence intentions. This study highlights that, as China's methamphetamine-addicted population rapidly expands, tailored treatment, especially facilitating positive peer support, is urgently needed.